The Influence of the Intergranular Superdisintegrant Performance on New Drotaverine Orodispersible Tablet Formulations - Robert-Alexandru Vlad; Cezara Pintea; Diana-Andreea Chirteș; Paula Antonoaea; Emöke Margit Rédai; Nicoleta Todoran; Magdalena Bîrsan; Adriana Ciurba (MDPI AG, 2023)
The main objective of this study consists in establishing the influence of the intergranular superdisintegrant on the specific properties of drotaverine hydrochloride fast-dissolving granules (DROT-FDGs) and orodispersible tablets (DROT-ODTs). The orodispersible tablets were obtained by the compression of the FDGs and excipient mixture with an eccentric tableting machine. To develop DROT-ODTs, two types of superdisintegrant excipients in different concentrations (water-soluble soy polysaccharides (SSP) (1%, 5%) and water-insoluble soy polysaccharides-Emcosoy® STS IP (EMCS) (1%, 3%, 5%)) were used, resulting in five formulations (D1-D5). The DROT-FDGs and the DROT-ODTs were subjected to pharmacotechnical and analytical evaluation. All the orodispersible tablets obtained respect the quality requirements in terms of friability (less than 1%), crushing strength (ranging between 52 N for D2 and 125.5 N for D3), and disintegration time (<180 s). The in vitro release of drotaverine from ODTs showed that all formulations presented amounts of active substance released greater than 85% at 10 min. The main objective, developing 30 mg DROT-ODTs for children aged between 6 and 12 years by incorporating the API in FDGs, was successfully achieved.